Do ankle stabilizers influence dynamic stability in persons with functional ankle instability? - Jacobs, N.; Butcher-Mokha, M.; Ludwig, K.; Krkeljas, Z. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Ankle sprains are the most common injury in the physically active, and reoccurrence rate is high. Repetitive ankle sprains can cause functional ankle instability (FAI), leading to deficits in balance, strength, and stability. Sports medicine professionals prescribe and administer bracing and taping as extrinsic methods of enhancing ankle stability. What is not clear is how these methods affect neuromuscular control during dynamic movements in persons with FAI. The purpose of this study was to determine the effects of taping and bracing on time to stabilization (TTS), as a measure of dynamic stability, in persons with FAI during two landing tasks.